2014
DOI: 10.1111/ced.12372
|View full text |Cite
|
Sign up to set email alerts
|

Skin lesions in a patient with IgG4-related disease

Abstract: IgG4-related disease (IgG4-RD) is a newly recognized condition that is characterized by raised levels of serum IgG4, tissue infiltration of IgG4-positive plasma cells and presence of fibrosis. It affects multiple organs, including the pancreas, bile duct, and lacrimal and salivary glands. Skin lesions have rarely been reported, and those that have were described as distributed mainly in the head and neck region. We report a case of IgG4-RD with autoimmune pancreatitis and skin lesions on the trunk and limbs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…h,i,j). These histopathological findings and clinical symptoms in the present case were similar to previously reported skin lesions involved in IgG4‐RD . As the skin lesions in the present case are not prominent, they might be a manifestation of conditions other than IgG4‐RD.…”
Section: Discussionsupporting
confidence: 90%
“…h,i,j). These histopathological findings and clinical symptoms in the present case were similar to previously reported skin lesions involved in IgG4‐RD . As the skin lesions in the present case are not prominent, they might be a manifestation of conditions other than IgG4‐RD.…”
Section: Discussionsupporting
confidence: 90%
“…Many patients with IgG4-related skin symptoms are reported to be Asian middle-aged and older men. Some investigators have reported that skin lesions were unresponsive to topical corticosteroids (14,15). These features fit the present case.…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, some cases have appeared to involve only a single organ disorder as IgG4-RD. Some cases have been reported to involve organs not typically associated with IgG4-RD, such as the heart (a lesion caused complete atrioventricular block [ 8 ]), skin [ 9 ], superior vena cava [ 10 ], hard palate [ 11 ], small intestine [ 12 ], esophagus [ 13 ], and colon [ 14 ].…”
Section: Discussionmentioning
confidence: 99%